The future of marketing analytics in the sharing economy - Akter, Shahriar; Hani, Umme; Dwivedi, Yogesh K.; Sharma, Anuj (Industrial marketing management, 2022)
The rise of sharing economy has accelerated the growth of marketing analytics to match demand and supply in industrial markets. However, the conceptualization of marketing analytics remains unclear in the sharing economy. Theorizing market turbulence as the dark side of the sharing economy, this study presents a marketing analytics capability model using dynamic capabilities and contingency theories to advance thought and practice in industrial marketing research. Using a thematic analysis and a survey-based empirical study on B2B cloud sharing platforms (n = 252), the findings present pattern identification, real-time solutions and data governance as the antecedents of marketing analytics capability with its holistic effects on marketing agility and marketing effectiveness. The empirical findings further support the mediating role of marketing agility and the moderating impact of market turbulence on marketing analytics-effectiveness and marketing agility-effectiveness chain. Overall, our results contribute toward a more nuanced understanding of the dark side of market turbulence on marketing analytics capability dynamics in the sharing economy. •Marketing analytics capability includes pattern identification, real-time solutions and data governance.•Marketing analytics capability accelerates marketing agility and marketing effectiveness in the sharing economy.•Market turbulence, including technology, competitor and customer turbulence, is the dark side of a sharing economy.